Flexible composite film for shielding of microwave radiation. (2021) - Rathi, Vikas; Prasad, Brijesh; Panwar, Varij; Mishra, Varun
Abstract: Electromagnetic interference (EMI) disrupts the working of electronic devices and circuits. In this work materials have been exploited in the form of conducting polymer composite film to give effective EMI shielding properties. Pre localized Graphite(Gr) powder will be mixed with Poly vinylidene fluoride (PVDF) and Ionic Liquid (IL) using solvent blending method to form a series of PVDF/Gr/IL composite films with different concentration of Gr and IL. Obtained films were characterized with Scanning Electron Microscopy (SEM) and Differential scanning calorimetry (DSC) for surface morphology and thermal analysis. The dielectric properties of the film were measured through which shielding effectiveness of the film is calculated for both near field and far field region in the frequency range of 100 KHz to 10 MHz. The composition with 70/10/20 exhibits maximum shielding effectiveness of 35 dB, 120 dB and 40 dB for plane wave, electric field and magnetic field respectively. The fabricated films exhibit excellent EMI Shielding properties with extra advantage of low cost and flexibility.